ARCHAEOLOGICAL AND CULTURAL IMPLICATIONS OF CPEC TOURISM DEVELOPMENT - Kausar Khan; Sohrab Ahmed Marri; Tahira Shaukat; Shahzada Muhammad Emaad Khan Durrani; Tariq Mahmood Awan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
ABSTRACT This study aims to investigate the archaeological and cultural implications of the China-Pakistan Economic Corridor (CPEC) tourism development. The CPEC project has resulted in significant economic and strategic development for China and Pakistan, but it is essential to consider the associated risks and limitations of tourism development projects to ensure successful implementation and maximize the potential benefits. The study emphasizes the importance of evaluating the impact of economic corridors on local communities, fostering regional cooperation, promoting tourism development, ensuring political stability, maintaining transparency, conducting environmental impact assessments, and managing debt. Additionally, the research highlights the potential for archaeological research and discoveries in the CPEC region and emphasizes the need for preservation strategies for historic sites and monuments. By considering these key factors, stakeholders and policymakers can draw on best practices and lessons learned from similar projects to ensure the success of the CPEC and other similar initiatives worldwide.